2019
DOI: 10.1007/s00134-019-05857-x
|View full text |Cite
|
Sign up to set email alerts
|

Conservative oxygen therapy for mechanically ventilated adults with sepsis: a post hoc analysis of data from the intensive care unit randomized trial comparing two approaches to oxygen therapy (ICU-ROX)

Abstract: Purpose: Sepsis is a common reason for intensive care unit (ICU) admission and mortality in ICU patients. Despite increasing interest in treatment strategies limiting oxygen exposure in ICU patients, no trials have compared conservative vs. usual oxygen in patients with sepsis. Methods: We undertook a post hoc analysis of the 251 patients with sepsis enrolled in a trial that compared conservative oxygen therapy with usual oxygen therapy in 1000 mechanically ventilated ICU patients. The primary end point for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
72
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 88 publications
(78 citation statements)
references
References 19 publications
4
72
0
2
Order By: Relevance
“…Observational studies and a small, singlecenter RCT suggest that use of a conservative oxygen strategy may be safe and beneficial in pneumonia (60)(61)(62). Some evidence points to improved outcomes with reduced oxygen exposure in several diseases, but recent RCT results are conflicting (63)(64)(65)(66)(67). We intend to implement an oxygenation strategy that compares conservative to liberal oxygenation support, and harmonize with a large scale trial of all-comer ICU patients.…”
Section: Respiratory Support Domainsmentioning
confidence: 99%
“…Observational studies and a small, singlecenter RCT suggest that use of a conservative oxygen strategy may be safe and beneficial in pneumonia (60)(61)(62). Some evidence points to improved outcomes with reduced oxygen exposure in several diseases, but recent RCT results are conflicting (63)(64)(65)(66)(67). We intend to implement an oxygenation strategy that compares conservative to liberal oxygenation support, and harmonize with a large scale trial of all-comer ICU patients.…”
Section: Respiratory Support Domainsmentioning
confidence: 99%
“…While two randomized controlled trials found beneficial effect of avoiding hyperoxia [ 33 , 34 ], a recent large international multicenter trial demonstrated no effect of conservative oxygen therapy in a cohort of critically ill patients [ 35 ]. However, a subsequent sub-study raised the possibility of clinically important harm with conservative oxygen therapy in patients with sepsis [ 36 ].…”
Section: Pathophysiologymentioning
confidence: 99%
“…In randomized trials, "induced" hyperoxia (using 100% oxygen) increased 28-day mortality in septic shock patients [23], while critically ill patients randomized to a target arterial oxygen tension (PaO 2 ) of 70-100 mmHg had lower mortality compared to patients with a "conventional" target of PaO 2 up to 150 mmHg [24] in a single-center study. While a recent large international multicenter trial demonstrated no effect of conservative oxygen therapy in a diverse cohort of critically ill patients [25], a subsequent sub-study raised the possibility of clinically important harm with conservative oxygen therapy in patients with sepsis [26].…”
Section: Introductionmentioning
confidence: 99%